Ethics and Social Responsibility in Technology Innovation for Sustainability and Social Justice - Da Silva, Eugenia Brandao; Gani , Abdul (Bulletin of Science, Technology and Society, 2022)
The rapid development of technology has a significant impact on human life, both in economic, social and cultural aspects. Without a clear implementation of ethics and social responsibility, technology innovation can lead to various problems, such as privacy violations, algorithmic bias, digital inequality, and resource exploitation. This research highlights the importance of integrating ethical values in technology to ensure that innovations provide equitable and sustainable benefits to society. Through a literature review approach, this research examines the main challenges in the implementation of technology ethics as well as strategies that can be applied to overcome these problems. The results of research show that strict regulations, transparency in technology development, and increased digital literacy are key factors to create an ethical and socially responsible technology ecosystem. Collaboration between the government, private sector and civil society is needed to build ethical standards that can keep pace with dynamic technological developments. Awareness of the social impact of technology should also be raised through education and public involvement in technology ethics discussions. With a comprehensive approach, technology can develop as a tool that supports the advancement of civilization without compromising moral principles and social justice. The integration of ethics in technological innovation is not just an option, but a necessity to create a more inclusive and sustainable future.